2015
DOI: 10.1371/journal.pone.0119648
|View full text |Cite
|
Sign up to set email alerts
|

Forces and Straw Cutting Performance of Double Disc Furrow Opener in No-Till Paddy Soil

Abstract: Conservation tillage is an energy efficient and low cost tillage system to improve soil environment compared with conventional tillage systems. However, the rice residue management becomes an “impossible to achieve” task due to high soil moisture content at harvest time and the thickness of rice straw. Disc type furrow openers are used for both seed drilling as well as straw cutting during no tillage sowing. A study was conducted to evaluate the draft requirement and straw cutting performances of different siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
2
20
0
1
Order By: Relevance
“…The test results validate the soil cutting theory that tools with a larger working width produce larger cutting resistance [35]. Darmora and Pandey [39], Hasimu and Chen [29], and Ahmad et al [28] found the same results when they tested different types of furrow openers.…”
Section: Cutting Force (F)supporting
confidence: 71%
“…The test results validate the soil cutting theory that tools with a larger working width produce larger cutting resistance [35]. Darmora and Pandey [39], Hasimu and Chen [29], and Ahmad et al [28] found the same results when they tested different types of furrow openers.…”
Section: Cutting Force (F)supporting
confidence: 71%
“…Crop Science © 2020 Crop Science Society of America The development of seed drill technology and placement of seed directly in the soil has led to the practice of applying all the seed and fertilizer in a single field pass. Different seed drill openers have been designed with different capabilities of fertilizer placement (Ahmad, Weimin, Qishuo, Hussain, & Jabran, 2015;Aikins et al, 2018;Swanepoel et al, 2018). With tine openers, fertilizer is placed deeper than the seed, whereas disc openers generally place seed and fertilizer at the same depth.…”
Section: Introductionmentioning
confidence: 99%
“…However, the traction efficiency is affected by the presence of previous crop's stubble ( Kamimura et al, 2009;Altikat et al, 2013;Ahmad et al, 2015), tillage management practices (Furlani et al, 2008;McLaughlin et al, 2008), soil characteristics (Collins & Fowler, 1996;Canakci et al, 2009;Cepik et al, 2010), furrow depth (McLaughlin et al, 2008;Cepik et al,…”
Section: Introductionmentioning
confidence: 99%